2018
DOI: 10.3390/molecules23061430
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl Group and Vasorelaxant Effects of Perillyl Alcohol, Carveol, Limonene on Aorta Smooth Muscle of Rats

Abstract: The present study used isometric tension recording to investigate the vasorelaxant effect of limonene (LM), carveol (CV), and perillyl alcohol (POH) on contractility parameters of the rat aorta, focusing in particular on the structure-activity relationship. LM, CV, and POH showed a reversible inhibitory effect on the contraction induced by electromechanical and pharmacomechanical coupling. In the case of LM, but not CV and POH, this effect was influenced by preservation of the endothelium. POH and CV but not L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 48 publications
4
11
1
Order By: Relevance
“…Our data differ from what has been found for carveol on rat aorta, where a greater pharmacological potency was observed in the presence of K + [12]. However, it is noteworthy that differences in response can occur both between vessels from experimental animals (rodents) and humans, which may be due to distinctions between them in terms of physiology, types of receptors and the action of certain signaling pathways [15,23,28].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our data differ from what has been found for carveol on rat aorta, where a greater pharmacological potency was observed in the presence of K + [12]. However, it is noteworthy that differences in response can occur both between vessels from experimental animals (rodents) and humans, which may be due to distinctions between them in terms of physiology, types of receptors and the action of certain signaling pathways [15,23,28].…”
Section: Discussioncontrasting
confidence: 99%
“…Corroborating with our findings, Cardoso-Teixeira et al [12] demonstrated that carveol promoted relaxation in rat aortic preparations that were pre-contracted with BayK-8644. This suggests that this monoterpene may be acting by inhibition of L-type Ca 2+ channels, since BayK-8644 is an agonist in L-type Ca 2+ channels [38].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Among the most prominent and therapeutically potentially promising activities of natural monoterpenes and monoterpenoids are those on the cardiovascular system [6]. Reports on literature, here reviewed and discussed, reveal their effect on heart (rate and inotropism), systemic blood pressure (SBP), and blood vessels (direct (myogenic) and indirect (endothelium mediated)) [7][8][9][10].…”
Section: Terpenes and Terpenoidsmentioning
confidence: 99%